Language functions to communicate appraisal and child directed speech - Sereková, Kamila (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Language used by parents to communicate with children is characterized by specific features. Adults use different language in communicating with other adults than in communicating with children. This paper is focused on analysing authentic recordings of common spoken discourses in families related to specific situations and activities (for example, children getting ready for school, art and craft activities, sitting at the table, etc.). The analysis will focus on examining the illocutionary language functions used to communicate the child’s appraisal (mainly praise, criticism, reproach), i.e. on the parent’s intent to express the appraisal of a child. The analysis draws upon the frequency of illocutionary language functions (in the whole sample, in pre-defined age categories of children, in specific activities offering examples of spoken discourse); further, the indication of illocutionary functions as expressed in the spoken discourse will be explored.
Keywords: spoken discourse; interaction; child directed speech; illocutionary language functions; praise; critisism